Peran Penggunaan Second Account Instagram dalam Mengurangi Tekanan untuk Mengikuti Standar di Media Sosial pada Gen Z - Faaizah Syafara Zuhrah; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Instagram has become a widely used social media platform for Gen Z to cultivate a self-image and gain social recognition. However, the pressure to portray an ideal life often leads to digital social pressure. This has prompted the use of "second accounts" as alternative spaces that are more private and authentic. This study aims to analyze the role of Instagram second accounts in alleviating the pressure Gen Z faces to conform to social media standards. Employing a descriptive qualitative method, data were collected through in-depth interviews with Gen Z individuals who are active Instagram users and possess a second account. The findings indicate that second accounts serve as a more comfortable and secure space for users to express themselves freely and authentically, without the fear of negative judgment from others. Furthermore, second accounts help users reduce social pressure and maintain a balance between their public and personal identities on social media. Thus, a second account functions not merely as an additional account but also as a digital communication strategy for Gen Z in navigating social pressures within the digital realm.